2013
DOI: 10.1002/cnm.2556
|View full text |Cite
|
Sign up to set email alerts
|

Multiphysics computational models for cardiac flow and virtual cardiography

Abstract: A multiphysics simulation approach is developed for predicting cardiac flows as well as for conducting virtual echocardiography (ECHO) and phonocardiography (PC) of those flows. Intraventricular blood flow in pathological heart conditions is simulated by solving the three-dimensional incompressible Navier-Stokes equations with an immersed boundary method, and using this computational hemodynamic data, echocardiographic and phonocardiographic signals are synthesized by separate simulations that model the physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
(68 reference statements)
1
27
0
Order By: Relevance
“…Past studies have shown that by choosing appropriate inlet information together with global geometric and flow parameters that are within physiological range, computational models with simplified valve structures can reproduce the flow features associated with LV function with reasonably accuracy 29, 35, 38, 57, 58 . It is well known that for a computational heart model to become a clinically relevant simulation tool it must be able to capture the FSI between the blood flow and the heart valves 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that by choosing appropriate inlet information together with global geometric and flow parameters that are within physiological range, computational models with simplified valve structures can reproduce the flow features associated with LV function with reasonably accuracy 29, 35, 38, 57, 58 . It is well known that for a computational heart model to become a clinically relevant simulation tool it must be able to capture the FSI between the blood flow and the heart valves 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, vortical instabilities and pressure fluctuations induced near the lumen wall have been described as a source of audible sound that can be auscultated at the aortic root (Seo et al, 2013). While arterial stenosis and Seo's work explicitly reference unstable flow, the results presented here are expected to represent stable flow due to the low, steady flow rates imposed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work, starting from the numerical results, virtual Echocardiographic and Phonocardiographic signals were synthetized, showing the feasibility to reproduce in silico the data normally acquired in the clinical practice. 88 …”
Section: Patient-specific Modelsmentioning
confidence: 99%